Tree Planting in Canterbury, New Zealand, 1850-1910. (1st November 2008) - Star, Paul
Abstract : One hundred and fifty years ago, T.H. Potts (1824-1888) tried to save the totara forests near Christchurch, and in Parliament he made conservation of native bush a national issue. At the same time, he sought the development of New Zealand through the introduction of exotics. Potts was among the first to suggest public plantations of exotic forest trees and he experimented on his estate with Monterey pine (Pinus radiata) and Monterey cypress (Cupressus macrocarpa). As a member of the Canterbury Plantation Board from its foundation in 1879 until his death, he participated in a pioneering attempt to improve the environment through exotic afforestation. Starting with consideration of Potts's contribution, this paper looks at early experimentation with tree planting in Canterbury and its encouragement, which predated attempts elsewhere in New Zealand. It stresses the role of individuals like Potts through to T.W. Adams (1842-1919) and of initiatives at the provincial (Canterbury) level. These activities have tended to be underplayed or overlooked by those tracing the late nineteenth century record of central government's fitful involvement in forestry and tree planting.